Front Cover: Highly Oriented Magnetic Film Composed of Ga‐Substituted ε‐Iron Oxide and the Angular Dependence of the Magnetic Hysteresis Loops (Eur. J. Inorg. Chem. 7/2018). Issue 7 (19th December 2017) - Yoshikiyo, Marie; Namai, Asuka; Imoto, Kenta; Tokoro, Hiroko; Ohkoshi, Shin‐ichi
Abstract : The Front Cover shows a crystallographically oriented film based on metal‐substituted ε‐iron oxide (ε‐Ga0.45 Fe1.55O3 ) magnetic nanoparticles. The a ‐axis of the orthorhombic crystal structure ( Pna2 1 space group) is oriented out of the plane of the film. The angular dependence of the magnetic hysteresis loop shows a rectangular hysteresis loop with a coercive field of 9.7 kOe and a magnetization of 30.4 emu g –1 at room temperature when the external field is along the out‐of‐plane direction with respect to the plane of the film, indicating that the easy axis corresponds to the crystallographic a ‐axis. More information can be found in theCommunication by H. Tokoro, S. Ohkoshi et al. For more on the story behind the cover research, see theCover Profile .